The Silver Sword - Serraillier, Ian; Escott, John (Oxford :Oxford Bookworms Library, 2007)
Jan opened his wooden box and took out the silver sword. 'This will bring me luck,' he said to Mr Balicki. 'And it will bring you luck because you gave it to me.' The silver sword is only a paper knife, but it gives Jan and his friends hope. Hungry, cold, and afraid, the four children try to stay alive among the ruins of bombed cities in war-torn Europe. Soon they will begin the long and dangerous journey south, from Poland to Switzerland, where they hope to find their parents again.
BAC
Keywords: Drama familiar; Aventuras; II Guerra Mundial; Nazismo; Polonia